Alteration of antibiotic regimen as an additional control measure in suspected multi-drug-resistant Enterobacter cloacae outbreak in a neonatal intensive care unit. Issue 2 (February 2020) - Eichel, V.; Papan, C.; Boutin, S.; Pöschl, J.; Heeg, K.; Nurjadi, D.
Summary: Background: Increased occurrence of a particular species of Gram-negative bacteria (GNB), especially when multi-drug-resistant (MDR), in routine screening surveillance in neonatal intensive care units (NICUs) can be evoked by selection pressure. Aim: To evaluate adaptation of the empiric antibiotic regimen for its usefulness as a control measure in suspected outbreaks in the NICU. Methods: In a retrospective outbreak analysis, cases between 1 st December 2017 and 31 st March 2018 were identified through microbiology and hygiene surveillance records. Furthermore, risk factors for MDR-GNB colonization were collected. Whole-genome sequencing (WGS) was performed on all isolates. Control measure documentations and interviews were employed to define interventions. As well as infection control measures, administration of third-generation cephalosporins was avoided and replaced whenever clinically acceptable as part of the intervention bundle. Findings: In total, nine patients were found to have rectal colonization with third-generation cephalosporin-resistant Enterobacter cloacae in routine screening surveillance in the pre-intervention period. After implementation of an infection control bundle, the incidence declined rapidly. WGS analysis revealed that two MDR E. cloacae were transmitted, and the majority were new cases. The incidence density of MDR-GNB colonization was 7.94/1000 patient-days (PD) before the intervention and 1.68/1000 PD during the altered antibiotic regimen. No infections with MDR-GNB occurred during the study. Conclusions: Altering the antibiotic regimen with regard to selection pressure may be considered as part of an intervention bundle to rapidly control the emergence of MDR-GNB in suspected outbreak situations in the NICU.